A Model of Worker Investment in Safety and Its Effects on Accidents and Wages - José R. Guardado; Nicolas Ziebarth (Institute for the Study of Labor (IZA), 2013)
In this paper, we develop a theoretical model of worker investment in safety. Standard theory assumes that injury risk is exogenous. It predicts that riskier jobs are associated with higher wages. In contrast, in our model, workers make individual safety investments that reduce the risk of injury. This results in a negative association between individual injury risk and wages. We test the model's predictions using obesity as a proxy for worker disinvestments in human capital and safety. In line with our model predictions, we find a significant positive compensating wage differential (CWD) for nonfatal risk at the occupational level. At the same time, however, there exists an underlying significant negative association between individual accident risk and wages, but only in high risk occupations. The latter relationship may downward bias or mask CWD estimates.
Keywords: I10; I12; J24; J31; J62; J71; 330; worker investment; safety; nonfatal risk; compensating wage differential; obesity